Overexpression of Full-Length ETV1 Transcripts in Clinical Prostate Cancer Due to Gene Translocation - Gasi, Delila (Public Library of Science, 2011)
ETV1 is overexpressed in a subset of clinical prostate cancers as a fusion transcript with many different partners. However, ETV1 can also be overexpressed as a full-length transcript. Full-length ETV1 protein functions differently from truncated ETV1 produced by fusion genes. In this study we describe the genetic background of full-length ETV1 overexpression and the biological properties of different full-length ETV1 isoforms in prostate cancer. Break-apart FISH showed in five out of six patient samples with overexpression of full-length ETV1 a genomic rearrangement of the gene, indicating frequent translocation. We were able to study the rearrangements in more detail in two tumors. In the first tumor 5′-RACE on cDNA showed linkage of the complete ETV1 transcript to the first exon of a prostate-specific two exon ncRNA gene that maps on chromosome 14 (EST14). This resulted in the expression of both full-length ETV1 transcripts and EST14-ETV1 fusion transcripts. In chromosome spreads of a xenograft derived from the second prostate cancer we observed a complex ETV1 translocation involving a chromosome 7 fragment that harbors ETV1 and fragments of chromosomes 4 and 10. Further studies revealed the overexpression of several different full-length transcripts, giving rise to four protein isoforms with different N-terminal regions. Even the shortest isoform synthesized by full-length ETV1 stimulated in vitro anchorage-independent growth of PNT2C2 prostate cells. This contrasts the lack of activity of even shorter N-truncated ETV1 produced by fusion transcripts. Our findings that in clinical prostate cancer overexpression of full-length ETV1 is due to genomic rearrangements involving different chromosomes and the identification of a shortened biologically active ETV1 isoform are highly relevant for understanding the mechanism of ETV1 function in prostate cancer.